A Further Contribution to the Study of Nursery Behaviour of Diospyros marmorata R.N. Parker (Marblewood) - Sharma, S. K. (Indian Forester, 1977)
The results of the trials and experiments conducted with this species for studying the viability, germination percent and plant percent with different seed treatments and seeds sown after different periods from the date or collection of fruits have been given. The viability period of seeda of this species goes hardly beyoud 20 days. For comparison, the seeds collected from Betapur were given the same treatment as those from Boroinyol, and it was found that Betapur seeds had better viability and germination. The treatment given to seeds by soaking them is cold or hot water did not improve the germination. The plants planted ia May survived better than the plants planted in June and afterwards. The survived plants also suffered further during the first summer (dry) months from February onwards.